BIOLOGICAL ASPECTS OF FOURFINGER THREADFIN, ELEUTHERONEMA TETRADACTYLUM (SHAW, 1804) CAUGHT IN LEKOK WATERS, PASURUAN, EAST JAVA - Lelono, Tri Djoko; Tumulyadi, Agus; Sari, Wahida Kartika; Ismaningsih, Indri Sari (Directorate of Research and Community Service (DRPM), 2021)
Fourfinger threadfin Eleutheronema tetradactylum has a local name, namely laosan fish by the coastal community of Lekok Pasuruan District, a type of demersal fish that can swim in brackish waters. This research aimed to determine the biological aspects, namely the relationship of Length to Weight, sex ratio, and to determine the feasibility of catching based on the measurement results of the length of the first caught (Lc) and the length of the gonads first ripened (Lm). This research was conducted based on catches during Januari - March 2020 for total samples of as much as 450 fish, based on the catch of gill nets. The result informed that the length and weight relationship was negative allometric. The sex ratio between male and female was 1.00: 0.00. During the study, no female gonads were found because the fourfinger threadfin had spawned protandrous hermaphrodites. The value of length at first maturity (Lm) and length at first capture (Lc) was 20.99 ± 0.13 cm and 24.66 ± 0.046 cm. Lc > Lm's value proves that the fish caught is dominant gonad ripe fish so that the fish is suitable for catching and the fishing gear used selectively.